Routine hospital screening tool (nrs-2002) is adequate for identifying malnourished dialysis patients in malaysia. - Tilakavati Karupaiah; Winnie Chee SS; Sharmela Sahathevan; Harvinder Kaur; Ali Jafarzadeh Esfehani; Leonard Joseph; Ghazali Ahmad; Sunita Bavanandan; Goh Bak Leong (The Korean Society of Nephrology, 2012)
Malnutrition is prevalent (>50%) in maintenance hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) patients in Malaysia. The priority is to identify a suitable nutritional screening tool for use in dialysis units. We conducted a study between June to November 2011 testing simplified nutritional screening tools on 155 HD and 90 CAPD patients to validate their potential application. Routine nutritional screening tools commonly used for hospitalized patients (NRS-2002, MST, MUST) were compared against tools specific to dialysis such as the malnutrition-inflammation score (MIS), modified Subjective Global Assessment (mSGA) and geriatric nutritional risk index (GNRI) with diagnostic values inclusive of anthropometry, biochemistry and dietary itnake. The mSGA compared to MIS indicated greater specificity for BMI<25 kg/m2, serum albumin<40 g/dL, AMA≤15th percentile, energy intake <30 kcal/kg/day and protein intake <1.2 g/kg/day with greater sensitivity scoring (99.3 vs 80.4%, 98.6 vs 72.9%, 99.3 vs 72.9%, 98.2 vs 67.3%, 98.3 vs 68.5% respectively). Comparing hospital screening tools against mSGA or MIS as reference standards for both PD and CAPD patients, the receiver operating characteristic (ROC) curve analysis indicated greater sensitivity in predicting malnutrition was associated with NRS (averaging at 58% against mSGA and 69% against MIS) whilst all other instruments were less predictive. GNRI, developed for Japanese dialysis patients was least sensitive to detect malnutrition. In conclusion, NRS-2002 can be utilized for identifying malnourished dialysis patients in Malaysia.